Tropical gastrointestinal disease: hepatosplenic schistosomiasis--pathological, clinical and treatment review - Shekhar, K.C. (Stamford Publishing Pte Ltd / Singapore Medical Association, 1994)
S. mansoni and S. japonicum complex schistosomes cause hepatosplenic and hepatointestinal schistosomiasis. The prevalence and incidence of this disease is increasing in all the endemic areas. Hepatosplenic schistosomiasis is seen in a small subset of clinically infected patients and represents a good model of intrahepatic portal hypertension characterised by a presinusoidal portal block and a well preserved liver parenchyma. Symmers' fibrosis is seen in a significant proportion of patients with high worm load. While the pathogenesis of Symmers' pipe stem fibrosis has not been well established, experimental and clinical data point to egg induced granulomata. The main consequences are presinusoidal portal hypertension, oesophageal varices and hepatosplenomegaly. The most striking symptoms are haematemesis or melena secondary to variceal and gastrointestinal bleeding. Cofactors associated with the pathogenesis include aflatoxins, malnutrition, alcoholism, hepatitis B and C virus. While stool examination is the best technique for diagnosis, a number of immunological tests though sensitive are not specific. Ultrasonography is sensitive for detection of Symmer's fibrosis. Praziquantel and oxaminiquine are drugs found to be effective in the treatment of hepatosplenic schistosomiasis. Recently beta-blockers have been found to be effective in the treatment of gastrointestinal rebleeding. Endoscopic sclerotherapy has been found to be effective for treatment of bleeding oesophageal varices. The treatment of choice for portal hypertension is oesophagogastric devascularization with splenectomy (EGDS).